Subordinate debt, deposit insurance and market oriented monitoring of banks - Gaurav S. Chauhan; Satyam S. Sundaram (IIMB Management Review, 2016)
We present a model of a bank with endogenous risk choices, where delegated monitoring by an active market in subordinate debt helps in containing the bank's risk shifting in the presence of deposit insurance. In comparison to static ex ante contracting, an active market enables continuous monitoring by subordinate debt to penalise the bank's risk shifting. The model is instrumental in deriving optimal level of subordinate debt required to achieve equilibrium where banks choose risk levels consistent with the first best as envisaged by a social planner. The optimal quantity of subordinate debt further eliminates any risk shifting associated even with risk insensitive premiums.